ON IMPROVING THE MATHEMATICAL TRAINING OF PEDAGOGICAL STUDENTS BASED ON TEACHING COMPUTER GRAPHICS AND MULTIMEDIA TECHNOLOGY - Duisebaeva А.Б. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
In this paper, an attempt is made to study the features of teaching future mathematics teachers in computer graphics and multimedia in the context of informatization of education and to identify some important points that affect the effectiveness of improving their mathematical training. Today, despite the abundance of various application software packages, the problem of learning computer animation remains relevant. The use of computer graphics in educational systems not only allows you to increase the speed of information transfer and increase its level of understanding, but also contributes to the development of imaginative thinking. Of great educational and psychological importance is the fact that the color of graphic images affects thoughts and feelings, stimulating the imagination. The competent use of computer graphics technology allows us to provide not only the best development of educational material, but also create all the conditions for a more effective learning process as a whole.